2016
DOI: 10.1128/jvi.02678-15
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an HIV-2 gp120 in Complex with CD4

Abstract: HIV-2 is a nonpandemic form of the virus causing AIDS, and the majority of HIV-2-infected patients exhibit long-term nonprogression. The HIV-1 and HIV-2 envelope glycoproteins, the sole targets of neutralizing antibodies, share 30 to 40% identity. As a first step in understanding the reduced pathogenicity of HIV-2, we solved a 3.0-Å structure of an HIV-2 gp120 bound to the host receptor CD4, which reveals structural similarity to HIV-1 gp120 despite divergence in amino acid sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…The differences between the slower and faster progressors with respect to positive selection at conserved sites were most highly pronounced in the C2 region (12 versus 3 sites, respectively) ( P = 0.021 [FET]), while such differences were not observed in the V1V2, V3, and C3 regions. To confirm previous observations that C2 is well exposed on the HIV-2 env gene, we used the published structural data of HIV-2 gp125 to visualize the amino acids in the V1-C3 region (24, 26). This analysis indicated that the majority (15 of 22) amino acids associated with positive selection mapped to exposed surfaces on HIV-2 gp125 (see Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The differences between the slower and faster progressors with respect to positive selection at conserved sites were most highly pronounced in the C2 region (12 versus 3 sites, respectively) ( P = 0.021 [FET]), while such differences were not observed in the V1V2, V3, and C3 regions. To confirm previous observations that C2 is well exposed on the HIV-2 env gene, we used the published structural data of HIV-2 gp125 to visualize the amino acids in the V1-C3 region (24, 26). This analysis indicated that the majority (15 of 22) amino acids associated with positive selection mapped to exposed surfaces on HIV-2 gp125 (see Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The Env protein complex mediates attachment to and entry into target cells first through recognition of CD4 + initiating a cascade of conformation reorganization of the Env protein complex that ultimately leads to the fusion of the viral envelope with the host cellular membrane and infection ( Fig. 2 D) ( Jones et al., 1998 , Davenport et al., 2015 ). Lectins are considered HIV entry inhibitors as they interact with the glycosylation moieties of the Env protein complex preventing the conformational rearrangements required for viral fusion ( Barrientos et al., 2006 ).…”
Section: Molecular Mechanisms Of Antiviral Lectinsmentioning
confidence: 99%
“…This finding would be supported by the hypothesized open structure of the HIV-2 V3 loop, which might reduce the role of interactions among the amino acids in the V3 loop [27]. Determining and analyzing the structure of gp125 with an intact and ordered V3 loop would be a crucial step in confirming the independence of positions by elucidating the accessibility of the V3 loop [50]. …”
Section: Discussionmentioning
confidence: 99%